PLANNING AND CONTROL FOR TIMBER CONSTRUCTION: STRATEGIES FOR EFFICIENCY AND SUSTAINABILITY (International Seven Journal of Multidisciplinary, 2025)
Timber construction has emerged as a leading approach in sustainable building practices due to its renewable nature and carbon storage capabilities. This article explores the critical aspects of planning and controlling timber construction, focusing on efficiency, sustainability, and addressing specific challenges. Key considerations such as Building Information Modeling (BIM), prefabrication, moisture management, regulatory compliance, and project control mechanisms are discussed. The article underscores the importance of leveraging technology and sustainability strategies to optimize the economic and environmental potential of timber construction.